2016
DOI: 10.4049/jimmunol.1500439
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Salmonid CD4+ T Cells

Abstract: This study reports the isolation and functional characterization of rainbow trout (Oncorhynchus mykiss) CD4-1+ T cells and the establishment of an IL-15–dependent CD4-1+ T cell line. By using Abs specific for CD4-1 and CD3ε it was possible to isolate the double-positive T cells in spleen and head kidney. The morphology and the presence of transcripts for T cell markers in the sorted CD4-1+CD3ε+ cells were studied next. Cells were found to express TCRα, TCRβ, CD152 (CTLA-4), CD154 (CD40L), T-bet, GATA-3, and ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 61 publications
4
50
0
Order By: Relevance
“…The sorted salmon IgM + cells were located in the low BF area and low SSC intensity gate, confirming a close area match to that of the lymphocyte-like cells. Similarly, a previous study on trout HK confirmed lymphocyte localization (low FSC and low SSC) using conventional FC, based on CD4 + T cell markers (26). In addition, employing conventional FC, percentage of IgM + and IgT + B cells in salmon HK cells were determined by gating the same area (25).…”
Section: Discussionmentioning
confidence: 63%
“…The sorted salmon IgM + cells were located in the low BF area and low SSC intensity gate, confirming a close area match to that of the lymphocyte-like cells. Similarly, a previous study on trout HK confirmed lymphocyte localization (low FSC and low SSC) using conventional FC, based on CD4 + T cell markers (26). In addition, employing conventional FC, percentage of IgM + and IgT + B cells in salmon HK cells were determined by gating the same area (25).…”
Section: Discussionmentioning
confidence: 63%
“…Rainbow trout contain two different sequences in their genome that seem to correspond to CD40L homologs, sharing an 81.44% amino acid identity ( Figure S3). Based on these results, in the current study, we focused on determining the levels of expression and the effects of one of these CD40L which was previously reported to be highly expressed in rainbow trout CD4 + T helper cells (37). Before determining the effect of CD40L on rainbow trout IgM + B cells, we verified which leukocyte subsets were expressing this CD40L in this species.…”
Section: Effect Of Cd40l On Teleost B Cellsmentioning
confidence: 85%
“…Interleukin‐10 is secreted inter alia by CD4 + T cells (Ng et al, ). These types of cells can also be found in the spleen of rainbow trout (Maisey et al, ). It remains unclear whether the immune‐modulating characteristics of the Ahiflower oil or the increased PUFA levels in the A66 and A100 diets per se might have affected the constitution of the spleen.…”
Section: Discussionmentioning
confidence: 97%